Comparison of dexamethasone intravitreal implant and intravitreal triamcinolone acetonide for the treatment of pseudophakic cystoid macular edema in diabetic patients - Dang Y; Mu Y; Li L; Mu Y; Liu S; Zhang C; Zhu Y; Xu Y (Dove Medical Press, 2014)
Yalong Dang,1,* Yalin Mu,2,* Lin Li,3,* Yahui Mu,2 Shujing Liu,2 Chun Zhang,4 Yu Zhu,1 Yimin Xu4 1Department of Ophthalmology, the First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan Province, 2Department of Ophthalmology, Yellow River Hospital, Henan University of Science and Technology, Sanmenxia, Henan Province, 3Department of Ophthalmology, the First Affiliated Hospital of Henan University of Science and Technology, Luoyang, Henan Province, 4Department of Ophthalmology, Peking University Third Hospital, Haidian District, Beijing, People's Republic of China *These authors contributed equally to this work. Background and objective: Our objective was to investigate the efficacy and safety of dexamethasone (DEX) implant for the treatment of pseudophakic cystoid macular edema (PCME) in diabetic patients. Study design: This was a prospective, non-randomized, interventional case series of 43 participants. Eighteen patients were enrolled in the DEX implant group and 25 were enrolled in an intravitreal triamcinolone acetonide (IVTA) group. Main outcome measures: The primary efficacy measurement was the percentage of patients who gained improvements of more than ten letters in best corrected visual acuity (BCVA) during 6 months of follow-up. Other efficacy measurements included change in BCVA, change in central macular thickness (CMT), and number of retreatments. The primary safety evaluation was the percentage of patients with intraocular hypertension and variation in intraocular pressure (IOP) during 6 months of follow-up. Other adverse events, such as conjunctival hemorrhage, eye pain, secondary infection, endophthalmitis, noninfectious inflammation, retinal detachment, and implant migration, were also recorded during follow-up. Results: At month 1, we observed that the percentage of patients gaining improvement of more than ten letters was similar in both groups (P=0.625). As patients in the IVTA group were retreated several times, this effect persisted throughout the study (P=0.941 at month 2, P=0.553 at month 3, P=0.856 at month 6). Variations in CMT were noticed at week 1 and reached their maximum at month 1. No significant difference was found between the two groups (P=0.831 at week 1, P=0.783 at month 1). At month 1, the variation in IOP reached its maximum in the DEX implant group and then decreased slightly. However, in the IVTA group, it increased continuously throughout the study. Conjunctival hemorrhage and eye pain were found in both groups, but both were rated as mild in severity, and no significant difference was found (P=0.184, P=0.766, respectively). Conclusion: Both IVTA and DEX implants could effectively restore visual function and recover morphological change in diabetic patients with PCME for at least 6 months, but repeated intravitreal injection was required in the IVTA group. DEX implant is well tolerated. We suggest that intravitreal injection of DEX implant is a promising new therapeutic option for diabetic patients with PCME. Keywords: dexamethasone implant, intravitreal triamcinolone acetonide, pseudophakic cystoid macular edema, diabetic retinopathy, corticosteroid, inflammation